АНАЛІЗ ЕФЕКТИВНОСТІ МЕТОДІВ ПІДВИЩЕННЯ ВІДНОШЕННЯ СИГНАЛ - ШУМ У ВИМІРЮВАЛЬНИХ СИСТЕМАХ З ДАТЧИКАМИ ІМПУЛЬСНИХ СТРУМІВ - Шидловська, Н.А.; Захарченко, С.М.; Мазуренко, І.Л. (Інститут електродинаміки Національної академії наук України, 2020)
In the paper the main methods of increasing the ratio of the useful signal to noise when measuring pulsed electric currents are analyzed. A comparative analysis of the advantages and disadvantages of the main types of current sensors is given. The test bench and the methodology for experimental studies of the influence of the parameters of the measuring system on the level of noise and disturbance when measuring pulsed electric currents are described. Modes in which in laboratory conditions the ratio of the level of the useful signal to noise is greatest are determined. The mechanism of the influence of the value of the active electrical resistance of a resistive current sensor on the signal-to-noise ratio at a high sensitivity of the oscilloscope is disclosed. The efficiency of shielding the current sensor and its grounding in some modes and their inefficiency in others to increase the signal-to-noise ratio has been experimentally proved. Practical recommendations for improving the signal-to-noise ratio in systems with analog pulse current sensors are given. References 39, tables 2.